Teach Aquaculture Curriculum: Introduction - Cortney L. Ohs; R. Leroy Creswell; Amber L. Garr; Carlos V. Martinez; Brian E. Myers; Elisa J. Livengood; Craig S. Kasper; Frank A. Chapman (EDIS)
FA177, a 2-page fact sheet by Cortney L. Ohs, R. Leroy Creswell, Amber L. Garr, Carlos V. Martinez, Brian E. Myers, Elisa J. Livengood, Craig S. Kasper, and Frank A. Chapman, introduces the Teach Aquaculture Curriculum. The curriculum is designed to engage students in aquaculture and the aquatic sciences through a series of hands-on activities involving all the sciences, mathematics, reading, and writing. Each activity in the series includes student performance standards. Published by the UF School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, July 2010.